Beyond marginality : Anglo-Jewish literature after the Holocaust - Sicher, Efraim (SUNY series on modern Jewish literature and culture., 1985)
A study of the effects of antisemitism, the Holocaust, and the search for Jewish identity on Anglo-Jewish writers. Pre-World War II literature reflected the antisemitism of working-class Jewish districts, while many postwar writers describe the inability of middle-class Jews to integrate fully into English society.